2018
DOI: 10.1177/0148558x18787118
|View full text |Cite
|
Sign up to set email alerts
|

Acquirers’ Cultural Background and the Use of Earnouts

Abstract: This study investigates the effects of culture on the design of merger and acquisition (M&A) contracts. Specifically, we empirically analyze how the acquirer’s cultural background influences the contractual choice to implement an earnout. We operationalize the acquirer’s cultural background by using Hofstede’s country-level indices for individualism, power distance, uncertainty avoidance, masculinity, and long-term orientation. Using a comprehensive sample of 9,669 M&As, we find that earnout use is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…While studies in this frontier examine a variety of mechanisms/devices for mitigating information asymmetry, including the use of stock (Cheng et al, 2022), contingent considerations such as earnouts (Battauz et al, 2021), seller financing (Jansen, 2020), earnings smoothing (Doukas & Zhang, 2020), sharing of same industry between acquirers and targets (Perafán‐Peña et al, 2022) and other contracting and signalling mechanisms in acquisitions, the predominant focus has been on earnouts. In particular, the research in this cluster documents that in addition to information asymmetry, the acquirer's cultural background (Ewelt‐Knauer et al, 2021), acquirer's earnings quality (Prencipe & Viarengo, 2022) and change in accounting standards (Chaney et al, 2020) can also influence the use of earnouts as a payment method in acquisitions. Further, acquirers that are larger, older, advised by top‐tier/boutique firms, and also those that make acquisitions of unlisted targets benefit more from the use of earnouts (Barbopoulos & Danbolt, 2021).…”
Section: Research Fronts and Future Directionsmentioning
confidence: 99%
“…While studies in this frontier examine a variety of mechanisms/devices for mitigating information asymmetry, including the use of stock (Cheng et al, 2022), contingent considerations such as earnouts (Battauz et al, 2021), seller financing (Jansen, 2020), earnings smoothing (Doukas & Zhang, 2020), sharing of same industry between acquirers and targets (Perafán‐Peña et al, 2022) and other contracting and signalling mechanisms in acquisitions, the predominant focus has been on earnouts. In particular, the research in this cluster documents that in addition to information asymmetry, the acquirer's cultural background (Ewelt‐Knauer et al, 2021), acquirer's earnings quality (Prencipe & Viarengo, 2022) and change in accounting standards (Chaney et al, 2020) can also influence the use of earnouts as a payment method in acquisitions. Further, acquirers that are larger, older, advised by top‐tier/boutique firms, and also those that make acquisitions of unlisted targets benefit more from the use of earnouts (Barbopoulos & Danbolt, 2021).…”
Section: Research Fronts and Future Directionsmentioning
confidence: 99%
“…State-contingent payments may be a useful tool to resolve potential valuation disagreements about private firms in M&A deals. In fact, Ewelt-Knauer et al (2021) report that 92% of targets in earnout deals are private firms.…”
Section: Earnout Agreements: Backgroundmentioning
confidence: 99%
“…Elnahas et al (2017) contended that earnouts violate Islamic law and, therefore, are infrequently used in Islamic countries. Ewelt-Knauer et al (2021) found that the use of earnouts is linked to the acquirer's cultural background, measured using Hofstede's country-level indices. The authors found that the use of earnouts is significantly negatively associated with the acquirer's power distance, a measure of organizational hierarchy, and uncertainty avoidance indices.…”
Section: Literature On Earnoutsmentioning
confidence: 99%